PENGARUH PEMBELAJARAN BERBASIS MASALAH TERHADAP PENINGKATAN SIKAP SELF-EFFICACY MAHASISWA - Tanti Jumaisyaroh Siregar (REKOGNISI : Jurnal Pendidikan dan Kependidikan, 2018)
The purpose of this study to determine: the effect of problem-based learning to improve the attitude of self-efficacy between students who were given with students and who were given direct learning. The type of this research is a quasi-experimental research by taking samples from the existing population. The variable of this research consist of independent variable that is problem based learning model while the dependent variable is self-efficacy attitude of student. This research was conducted at UMN Al-Washliyah Medan which is located at Jalan Garu II No. 52 Medan. This research will be conducted in the odd semester of the academic year 2017/2018. The population in this study is all students Mathematics Education Program of FKIP UMN Al-Washliyah Medan and the sample in this study are students of mathematics education program in the third semester by taking two classes that are III A and III B at random (experimental class and control class). Technique of collecting data in this research by using questionnaire. Questionnaire used is the scale of attitude self-efficacy (pretest and posttest). Data that have been collected then analyzed and performed hypothesis testing by using regression test. Based on the results of the analysis is obtained: there are effects of problem-based learning to improve student self-efficacy attitude. Therefore, it is suggested that problem-based learning be used as an alternative for lecturers to improve student self-efficacy attitude.